Effects of single phase sinusoidal voltage fluctuations related to flicker limits on three phase induction motors - Cruz, Carlos; Molina, Julio (Rev. Téc. Fac. Ing. Univ. Zulia, 2012)
Rapid voltage fluctuations may cause lamp flicker. Therefore, in some standards these voltage fluctuations have been regulated through the use of a limit value for the short term flicker severity index (Pst). The purpose of this work is to determine, using computer simulations, how the three phase induction motor is affected when a sinusoidal voltage fluctuation is present in one of the phases of the voltage source. The voltage fluctuation considered is such that produces a short term flicker severity index equal to one, which corresponds to the limit value. The motor is modeled using its dynamic equations, and the variables studied are torque and speed. The motivating drive for this research, is to provide new criteria, which in the future may help review the regulations on voltage fluctuations in the power quality standards.